Transcriptomic and proteomic profiling identifies feline fibrosarcoma as clinically amenable model for aggressive sarcoma subtypes - Mikiyo Weber; Daniel Fuchs; Amiskwia Pöschel; Erin Beebe; Zuzana Garajova; Armin Jarosch; Laura Kunz; Witold Wolski; Lennart Opitz; Franco Guscetti; Mirja C. Nolff; Enni Markkanen (Neoplasia: An International Journal for Oncology Research)
Fibrosarcomas (FSA) are malignant mesenchymal tumors characterized by low chemo- and radiosensitivity. Development of novel treatment strategies for human adult FSA is hindered by the low incidence and the absence of suitable clinical models. Interestingly, aggressive FSA occur more frequently in domestic cats, hence potentially representing a clinically amenable model to assess novel therapies such as targeted imaging or theranostics. However, a lack of molecular characterization of FSA and adjacent normal tissue (NT) in both species hinders identification of tumor-specific targets and undermines the translational potential of feline FSA. Combining laser-capture microdissection, RNAsequencing and liquid chromatography-tandem mass spectrometry, we perform comprehensive profiling of 30 feline FSA and matched skeletal muscle, adipose and connective tissue. Clear inter-tissue differences allow identification of significantly upregulated and tumor-exclusive features that represent potential targets for diagnostic and therapeutic approaches. While feline FSA are characterized by hyperactive EIF2, TP53 and MYC signaling, immune-related and neuronal pathways emerge as modulators of tumor aggressiveness and immunosuppression. A high degree of molecular similarity with canine and adult FSA allows identification of tumor targets that are conserved across species. Significant enrichment in DNA repair pathways in feline FSA correlate with aggressive clinical behavior in human soft-tissue sarcoma. Finally, we leverage the molecular profiles to identify vulnerabilities, including sensitivity to ATR and PARP inhibition as potential treatment for feline FSA. In conclusion, this detailed landscape provides a rich resource to identify target candidates and therapeutic vulnerabilities within and across species and supports feline FSA as relevant models for the human disease.